Clay composite membrane as well as preparation method and application thereof

By using clay composite membranes in membrane separation technology, the problems of in-situ degradation of pollutants and membrane contamination in the prior art are solved, and efficient micro-pollutant removal and membrane life are achieved.

CN119524643APending Publication Date: 2025-02-28TSINGHUA UNIVERSITY

Patent Information

Application Number
CN202411438644.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

When existing membrane separation technology treats micro-pollutants in water, it cannot achieve in-situ degradation of pollutants, and the accumulation of pollutants on the surface of the membrane will lead to membrane contamination and shortening of service life.

Method used

A clay composite membrane is used, which consists of a porous base film and a clay layer, which includes multi-layered single-layer clay nanosheets and attached transition metal ions, which can catalyze the degradation of microcontaminants in situ during membrane separation.

Benefits of technology

In-situ degradation of micro-contaminants is achieved, post-treatment steps are avoided, the service life of the membrane is extended, the treatment cost is reduced, and the stability of the membrane and its ability to resist acid, alkali and organic solvents are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119524643A_ABST
    Figure CN119524643A_ABST
Patent Text Reader

Abstract

The invention relates to a clay composite membrane and a preparation method and application thereof.The clay composite membrane comprises a porous basement membrane and a clay layer at least located on one side of the porous basement membrane, and the clay layer comprises multiple layers of stacked single-layer clay nanosheets and transition metal ions attached to the interlayers and the surfaces of the multiple layers of stacked single-layer clay nanosheets; the clay composite membrane has both separation and catalysis performance, and can degrade micropollutants in situ.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of functional films, and in particular to a clay composite film and a preparation method and application thereof. Background Art

[0002] Membrane separation technology can play a key role in the recycling of water resources and is known as the water treatment technology with the greatest development potential in the 21st century. The effluent of membrane water purification technology is almost unaffected by changes in the quality of the influent water, and can produce high-quality water. It is used in water treatment processes such as deep treatment of drinking water and removal of water pollutants. However, the membrane separation process only separates pollutants from polluted water bodies and cannot truly degrade pollutants. In the membrane-based water purification process, since pollutants will gradually deposit on the membrane surface or even inside the membrane pores, long-term use will often cause the membrane pores to become clogged, resulting in reduced water pressure and reduced effluent quality. Therefore, giving traditional membrane materials new properties and functions to achieve the simultaneous separation and degradation of micropollutants in water bodies is one of the problems that researchers are eager to solve.

[0003] Since the discovery of graphene materials in 2004, graphene and graphene-like two-dimensional nanomaterials have shown great application potential in environmental-related fields such as adsorption and catalysis. The membrane prepared by assembling two-dimensional graphene sheets layer by layer has excellent membrane separation performance, but there are many problems in the process of stripping the original graphite to obtain single-layer graphene and preparing other two-dimensional materials. For example, the preparation process requires a large amount of oxidants, acids, and bases, and the yield is relatively low, which limits the further promotion and application of two-dimensional materials. Clay minerals represented by vermiculite, montmorillonite, and mica have a uniform layered structure composed of silicon-oxygen tetrahedrons and aluminum-oxygen octahedrons, and are abundant in nature. Currently, vermiculite-based applications are mostly thermal insulation materials in the construction industry and agricultural fertilizers. Although the two-dimensional layered vermiculite membrane has excellent membrane separation performance, its retention performance for micropollutants such as bisphenol A and phenol needs to be studied. At the same time, the accumulation of pollutants on the membrane surface will cause membrane pollution, reducing the service life and screening performance of the membrane. Secondly, the retention process only separates the pollutants from the water body, and cannot achieve in-situ degradation of the pollutants. The pollutants still need to be degraded through post-treatment, which increases the treatment cost. Summary of the invention

[0004] The present application provides a clay composite membrane and a preparation method and application thereof. The clay composite membrane has both separation and catalytic properties and can degrade micropollutants in situ.

[0005] In a first aspect of the present application, a clay composite membrane is provided, comprising a porous base membrane and a clay layer at least located on one side of the porous base membrane, wherein the clay layer comprises multi-layer stacked monolayer clay nanosheets and transition metal ions attached to the interlayers and surfaces of the multi-layer stacked monolayer clay nanosheets.

[0006] In some embodiments, the transition metal ion comprises Co 2+ , Mn 2+ , Fe 2+ , Fe 3+ , Cu 2+ and Ni 2+ One or more of .

[0007] In some embodiments, the thickness of the clay layer is 15 nm to 500 nm.

[0008] In some embodiments, the thickness of the single-layer clay nanosheet is 0.5 nm to 2 nm.

[0009] In some embodiments, the single-layer clay nanosheet has a sheet diameter of 1 μm to 10 μm.

[0010] In some embodiments, the monolithic clay nanoplatelets include one or more of monolithic vermiculite nanoplatelets and monolithic montmorillonite nanoplatelets.

[0011] In some embodiments, the average pore size of the pore structure of the porous substrate membrane is 0.1 μm to 0.45 μm.

[0012] In some embodiments, the porous substrate membrane has a thickness of 2 μm to 500 μm.

[0013] In some embodiments, the material of the porous substrate membrane includes one or more of polyvinylidene fluoride, polyethersulfone and ceramic.

[0014] The second aspect of the present application provides a method for preparing a clay composite film, comprising the following steps:

[0015] The clay is placed in different solutions, and subjected to stirring and washing treatments to prepare a solution containing single-layer clay nanosheets;

[0016] Assembling the solution containing the monolayer clay nanosheets layer by layer on at least one side of the porous substrate membrane, and subjecting it to heat treatment, to obtain a two-dimensional clay membrane, wherein the two-dimensional clay membrane contains multiple layers of stacked monolayer clay nanosheets;

[0017] Placing the two-dimensional clay film in a transition metal salt solution, so that the transition metal ions in the transition metal salt solution adhere to the interlayers and surfaces of the multi-layer stacked single-layer clay nanosheets to form a clay layer, thereby obtaining the clay composite film;

[0018] The clay composite membrane comprises the porous substrate membrane and the clay layer at least located on one side of the porous substrate membrane, and the clay layer comprises the multi-layer stacked single-layer clay nanosheets and the transition metal ions.

[0019] In some embodiments, the transition metal ion comprises Co 2+ , Mn 2+ , Fe 2+ , Fe 3+ , Cu 2+ and Ni 2+ One or more of .

[0020] In some embodiments, the thickness of the clay layer is 15 nm to 500 nm.

[0021] In some embodiments, the thickness of the single-layer clay nanosheet is 0.5 nm to 2 nm.

[0022] In some embodiments, the single-layer clay nanosheet has a sheet diameter of 1 μm to 10 μm.

[0023] In some embodiments, the monolithic clay nanoplatelets include one or more of monolithic vermiculite nanoplatelets and monolithic montmorillonite nanoplatelets.

[0024] In some embodiments, the process conditions of the heat treatment include: the heat treatment temperature is 100° C. to 150° C., and the heat treatment time is 12 h to 48 h.

[0025] In some embodiments, the concentration of the solution comprising single-sheet clay nanosheets is 0.1 mg / mL to 1 mg / mL.

[0026] In some embodiments, the material of the porous substrate membrane includes one or more of polyvinylidene fluoride, polyethersulfone and ceramic.

[0027] In some embodiments, the step of assembling the solution containing monolithic clay nanosheets layer by layer on at least one side of a porous substrate membrane comprises: assembling the solution containing monolithic clay nanosheets layer by layer on at least one side of a porous substrate membrane by at least one method selected from the group consisting of filtration, spraying, drop coating, and spin coating.

[0028] In some embodiments, clay is placed in different solutions, and after stirring and washing, the steps of preparing a solution containing single-layer clay nanosheets include:

[0029] The clay is placed in a pretreatment solution, and subjected to stirring treatment and washing treatment in sequence to prepare intercalated clay;

[0030] The intercalated clay is dispersed in a solution containing a thermally decomposable substance, and the thermally decomposable substance is decomposed by heating to generate gas to peel off the intercalated clay, thereby obtaining the solution containing the single-layer clay nanosheet.

[0031] In some embodiments, the process conditions of the stirring treatment include: a stirring temperature of 25° C. to 120° C., and a stirring time of 12 h to 48 h.

[0032] In some embodiments, the process conditions of the heat treatment include: a heating temperature of 90° C. to 120° C. and a heating time of 12 h to 48 h.

[0033] In some embodiments, the clay includes one or more of thermally expanded vermiculite and montmorillonite, and the intercalated clay includes one or more of intercalated vermiculite and intercalated montmorillonite.

[0034] In some embodiments, the pretreatment solution includes one or more of a sodium salt solution, a lithium salt solution, and a surfactant solution.

[0035] In some embodiments, the sodium salt solution includes one or more of a sodium chloride solution, a sodium sulfate solution, a sodium carbonate solution, and a sodium bicarbonate solution.

[0036] In some embodiments, the lithium salt solution includes one or more of a lithium chloride solution, a lithium sulfate solution, and a lithium carbonate solution.

[0037] In some embodiments, the surfactant solution includes one or more of dodecyltrimethylammonium bromide solution, tetradecyltrimethylammonium bromide solution, hexadecyltrimethylammonium bromide solution, and octadecyltrimethylammonium bromide solution.

[0038] In some embodiments, the sodium salt solution is a saturated solution.

[0039] In some embodiments, the concentration of the lithium salt solution is 1 mol / L to 3 mol / L.

[0040] In some embodiments, the concentration of the surfactant solution is 1 mol / L to 3 mol / L.

[0041] In some embodiments, the thermally decomposable substance includes one or more of hydrogen peroxide and sodium bicarbonate.

[0042] In some embodiments, after the step of dispersing the intercalated clay in a solution containing a thermally decomposable substance and subjecting the thermally decomposable substance to heat treatment to decompose the thermally decomposable substance to generate gas to peel off the intercalated clay, the method further includes: washing the obtained product, and then sequentially subjecting the product to ultrasonic treatment, a first centrifugal treatment, and a second centrifugal treatment to remove the clay with a multilayer structure to obtain a solution containing single-layer clay nanosheets, wherein the rotation speed of the first centrifugal treatment is higher than the rotation speed of the second centrifugal treatment.

[0043] In some embodiments, the process conditions of the first centrifugal treatment include: a centrifugal treatment speed of 8000 rpm to 10000 rpm, and a centrifugal treatment time of 15 min to 30 min.

[0044] In some embodiments, the process conditions of the second centrifugal treatment include: a centrifugal treatment speed of 1000 rpm to 3000 rpm, and a centrifugal treatment time of 60 min to 180 min.

[0045] In some embodiments, the process conditions of ultrasonic treatment include: the ultrasonic treatment time is 30 min to 60 min.

[0046] The third aspect of the present application provides the use of the clay composite membrane described in the first aspect of the present application or the clay composite membrane prepared by the preparation method described in the second aspect of the present application in the preparation of separation catalytic membranes.

[0047] In a fourth aspect of the present application, a separation catalytic device is provided, comprising the clay composite membrane described in the first aspect of the present application or the clay composite membrane prepared by the preparation method described in the second aspect of the present application.

[0048] In some embodiments, the separation catalytic device further comprises one or more of hydrogen peroxide and persulfate.

[0049] Compared with traditional technologies, the above-mentioned clay composite membrane has at least the following advantages:

[0050] In the above-mentioned clay composite membrane, the porous base membrane can provide support for the clay layer. The clay layer has excellent membrane separation performance and can catalytically degrade micropollutants such as bisphenol A and phenol in situ. There is no need to post-treat the retained micropollutants, which is beneficial to alleviating membrane pollution and saving costs. The clay composite membrane is highly stable and resistant to acids, alkalis and organic solvents. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] FIG. 1 is an atomic force microscope image of the vermiculite nanosheets of Example 1.

[0052] FIG. 2 is a scanning electron microscope image of a cross section of the vermiculite composite membrane prepared in Example 1.

[0053] Figure 3 is a picture of the vermiculite composite film prepared in Example 1 immersed in an organic solvent, a 1M HCl solution and a 1M NaOH solution for 0 h and 24 h; (a) in Figure 3 is ethanol, (b) in Figure 3 is methanol, (c) in Figure 3 is n-hexane, (d) in Figure 3 is acetonitrile, (e) in Figure 3 is acetone, (f) in Figure 3 is 1M NaOH solution, and (g) in Figure 3 is 1M HCl solution.

[0054] Figure 4 is a picture of the monolayer montmorillonite nanosheet solution and the montmorillonite composite film prepared in step three of Example 7; Figure 4 (a) is a picture of the monolayer montmorillonite nanosheet solution prepared in step three, and Figure 4 (b) is a picture of the montmorillonite composite film.

[0055] Figure 5 is a picture of the montmorillonite composite membrane prepared in Example 7 immersed in water; Figure 5 (a) is a picture of the montmorillonite composite membrane immersed in water for 0 hours, and Figure 5 (b) is a picture of the montmorillonite composite membrane immersed in water for 7 days.

[0056] FIG6 is a picture of the vermiculite composite membrane prepared in Comparative Example 1 immersed in water.

[0057] FIG. 7 is a test diagram of the surface water contact angle of the vermiculite composite membranes prepared in Example 1, Examples 3 to 6 and Comparative Example 2.

[0058] FIG8 is a graph showing the surface potential test of the vermiculite composite membranes prepared in Example 1 and Examples 3 to 6.

[0059] FIG. 9 is an X-ray diffraction diagram of the vermiculite composite membranes prepared in Example 1 and Examples 3 to 6.

[0060] 10 is a bar graph showing the removal rates of bisphenol A by the vermiculite composite membranes prepared in Example 1, Examples 3 to 6 and Comparative Example 2, and the montmorillonite composite membrane prepared in Example 7. DETAILED DESCRIPTION

[0061] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail below. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.

[0062] In this application, "first aspect", "second aspect", "third aspect", etc. are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", "third", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.

[0063] In this application, "optionally", "optional", and "optional" mean optional or dispensable, that is, any one of the two parallel schemes of "yes" or "no". If multiple "options" appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent.

[0064] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0065] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0066] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as those commonly understood by technicians in the technical field of this application. The terms used in this application and in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used in this application includes any and all combinations of one or more related listed items. The term "multiple" in this application means at least two, such as two, three, etc., unless otherwise clearly and specifically limited.

[0067] An embodiment of the present application provides a clay composite membrane, comprising a porous base membrane and a clay layer at least located on one side of the porous base membrane, wherein the clay layer comprises multi-layer stacked monolayer clay nanosheets and transition metal ions attached to the interlayers and surfaces of the multi-layer stacked monolayer clay nanosheets.

[0068] In the above-mentioned clay composite membrane, the porous base membrane can provide support for the clay layer. The clay layer has excellent membrane separation performance and can catalytically degrade micropollutants such as bisphenol A and phenol in situ. There is no need to post-treat the retained micropollutants, which is beneficial to alleviating membrane pollution and saving costs. The clay composite membrane is highly stable and resistant to acids, alkalis and organic solvents.

[0069] As non-limiting examples, the clay layer in the clay composite membrane may be located on one side of the porous substrate membrane, or may be located on opposite sides of the porous substrate membrane.

[0070] In the present application, the interlayers of “multi-layer stacked monolithic clay nanosheets” refer to the spaces between multiple monolithic clay nanosheets, and the surface of “multi-layer stacked monolithic clay nanosheets” refers to the outer surface of the multi-layer stacked monolithic clay nanosheets.

[0071] In some embodiments, the transition metal ion includes Co 2+ , Mn 2+ , Fe 2+ , Fe 3+ , Cu2+ and Ni 2+ The clay composite membrane containing the above-mentioned transition metal ions can further improve the degradation ability of micro-pollutants, thereby further improving the removal rate of micro-pollutants.

[0072] In some embodiments, the thickness of the clay layer is 15 nm to 500 nm. Exemplarily, the thickness of the clay layer includes, but is not limited to, 15 nm, 50 nm, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm, or a range between any two of the foregoing.

[0073] In some embodiments, the thickness of the single-layer clay nanosheet is 0.5 nm to 2 nm. For example, the thickness of the single-layer clay nanosheet includes, but is not limited to, 0.5 nm, 0.8 nm, 1 nm, 1.2 nm, 1.5 nm, 1.8 nm, 2 nm, or a range between any two of the foregoing.

[0074] In some embodiments, the diameter of the single-layer clay nanosheet is 1 μm to 10 μm. For example, the diameter of the single-layer clay nanosheet includes but is not limited to: 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm or a range between any two of the foregoing.

[0075] In the present application, “the diameter of a single-layer clay nanosheet” refers to the average value of the maximum lateral dimension and the minimum lateral dimension of the single-layer clay nanosheet.

[0076] In some embodiments, the monolithic clay nanoplatelets include one or more of monolithic vermiculite nanoplatelets and monolithic montmorillonite nanoplatelets.

[0077] In some embodiments, the single-layer clay nanosheet is a single-layer vermiculite nanosheet, the clay layer is a vermiculite layer, and the clay composite film is a vermiculite composite film.

[0078] In some embodiments, the monolayer clay nanosheet is a monolayer montmorillonite nanosheet, the clay layer is a montmorillonite layer, and the clay composite film is a montmorillonite composite film.

[0079] In some embodiments, the average pore size of the pore structure of the porous substrate membrane is 0.1 μm to 0.45 μm. For example, the average pore size of the pore structure of the porous substrate membrane includes, but is not limited to, 0.1 μm, 0.15 μm, 0.2 μm, 0.25 μm, 0.3 μm, 0.35 μm, 0.4 μm, 0.45 μm, or a range between any two of the foregoing.

[0080] In some embodiments, the thickness of the porous substrate membrane is 2 μm to 500 μm. For example, the thickness of the porous substrate membrane includes, but is not limited to, 2 μm, 10 μm, 20 μm, 50 μm, 100 μm, 150 μm, 200 μm, 250 μm, 300 μm, 350 μm, 400 μm, 450 μm, 500 μm, or a range between any two of the foregoing.

[0081] In some embodiments, the material of the porous substrate membrane includes one or more of polyvinylidene fluoride, polyethersulfone and ceramic. Selecting the above materials can improve the stability of the porous substrate membrane.

[0082] Another embodiment of the present application provides a method for preparing a clay composite film, comprising the following steps:

[0083] The clay is placed in different solutions, and subjected to stirring and washing treatments to prepare a solution containing single-layer clay nanosheets;

[0084] Assembling a solution containing a single-layer clay nanosheet on at least one side of a porous substrate film layer by layer, and subjecting the solution to heat treatment to obtain a two-dimensional clay film, wherein the two-dimensional clay film contains multiple layers of stacked single-layer clay nanosheets;

[0085] Placing the two-dimensional clay film in a transition metal salt solution, so that the transition metal ions in the transition metal salt solution adhere to the interlayers and surfaces of the multi-layer stacked single-layer clay nanosheets to form a clay layer, thereby obtaining a clay composite film;

[0086] The clay composite membrane comprises a porous substrate membrane and a clay layer at least located on one side of the porous substrate membrane, wherein the clay layer comprises multi-layer stacked single-layer clay nanosheets and transition metal ions.

[0087] In the clay composite membrane prepared by the above preparation method, the porous base membrane can provide support for the clay layer, and the clay layer has excellent membrane separation performance. At the same time, it can catalytically degrade micropollutants such as bisphenol A and phenol in situ, without the need for post-treatment of the retained micropollutants, which is conducive to alleviating membrane pollution and saving costs. The clay composite membrane has high stability and can resist acids, alkalis and organic solvents. The above preparation method is easy to operate and simple in process, which is conducive to promotion and use.

[0088] In some embodiments, the temperature of the heat treatment is greater than or equal to 100° C. Controlling the temperature of the heat treatment to be greater than or equal to 100° C. is beneficial to improving the stability of the multi-layer stacked single-layer clay nanosheets in water.

[0089] In some embodiments, the transition metal ion includes Co 2+ , Mn 2+ , Fe 2+ , Fe 3+ , Cu 2+ and Ni2+ The clay composite membrane containing the above-mentioned transition metal ions can further improve the degradation ability of micro-pollutants, thereby further improving the removal rate of micro-pollutants.

[0090] In some embodiments, the thickness of the clay layer is 15 nm to 500 nm.

[0091] In some embodiments, the thickness of a single layer of clay nanosheet is 0.5 nm to 2 nm.

[0092] In some embodiments, the single-layer clay nanosheet has a sheet diameter of 1 μm to 10 μm.

[0093] In some embodiments, the monolithic clay nanoplatelets include one or more of monolithic vermiculite nanoplatelets and monolithic montmorillonite nanoplatelets.

[0094] In some embodiments, the process conditions of the heat treatment include: the temperature of the heat treatment is 100°C to 150°C, and the time of the heat treatment is 12h to 48h. Exemplarily, the temperature of the heat treatment includes but is not limited to: 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C or a range between any two of the foregoing, and the time of the heat treatment includes but is not limited to: 12h, 15h, 18h, 20h, 25h, 30h, 35h, 40h, 45h, 48h or a range between any two of the foregoing.

[0095] In some embodiments, the concentration of the solution containing the single-layer clay nanosheet is 0.1 mg / mL to 1 mg / mL. Exemplarily, the above concentration includes but is not limited to: 0.1 mg / mL, 0.2 mg / mL, 0.3 mg / mL, 0.4 mg / mL, 0.5 mg / mL, 0.6 mg / mL, 0.7 mg / mL, 0.8 mg / mL, 0.9 mg / mL, 1 mg / mL or a range between any two of the foregoing.

[0096] In some embodiments, the material of the porous substrate membrane includes one or more of polyvinylidene fluoride, polyethersulfone and ceramic.

[0097] In some embodiments, the step of assembling a solution containing monolithic clay nanosheets layer by layer on at least one side of a porous substrate membrane comprises: assembling a solution containing monolithic clay nanosheets layer by layer on at least one side of a porous substrate membrane by at least one of filtration, spraying, drop coating and spin coating.

[0098] In some embodiments, clay is placed in different solutions, and after stirring and washing, the steps of preparing a solution containing single-layer clay nanosheets include:

[0099] The heat-expandable clay is placed in a pretreatment solution, and subjected to stirring treatment and washing treatment in sequence to prepare intercalated clay;

[0100] The intercalated clay is dispersed in a solution containing a thermally decomposable substance, and the thermally decomposable substance is decomposed by heating to generate gas to peel off the intercalated clay, thereby obtaining a solution containing a single-layer clay nanosheet.

[0101] In some embodiments, the process conditions of the stirring treatment include: a stirring temperature of 25°C to 120°C, and a stirring time of 12h to 48h. Such a design is conducive to removing impurities. Exemplarily, the stirring temperature includes but is not limited to: 25°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C or a range between any two of the foregoing, and the stirring time includes but is not limited to: 12h, 15h, 18h, 20h, 25h, 30h, 35h, 40h, 45h, 48h or a range between any two of the foregoing.

[0102] In some embodiments, the process conditions of the heat treatment include: a heating temperature of 90°C to 120°C, and a heating time of 12h to 48h. Exemplarily, the heating temperature includes but is not limited to: 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, or a range between any two of the foregoing, and the heating time includes but is not limited to: 12h, 15h, 18h, 20h, 25h, 30h, 35h, 40h, 45h, 48h, or a range between any two of the foregoing.

[0103] In some embodiments, the clay includes one or more of thermally expanded vermiculite and montmorillonite, and the intercalated clay includes one or more of intercalated vermiculite and intercalated montmorillonite.

[0104] In some embodiments, the clay is thermally expanded vermiculite, the intercalated clay is intercalated vermiculite, the monolayer clay nanosheet is a monolayer vermiculite nanosheet, the clay layer is a vermiculite layer, and the clay composite film is a vermiculite composite film.

[0105] In some embodiments, the clay is montmorillonite, the intercalated clay is intercalated montmorillonite, the monolayer clay nanosheet is a monolayer montmorillonite nanosheet, the clay layer is a montmorillonite layer, and the clay composite film is a montmorillonite composite film.

[0106] In some embodiments, the sodium salt solution includes one or more of a sodium chloride solution, a sodium sulfate solution, a sodium carbonate solution, and a sodium bicarbonate solution.

[0107] In some embodiments, the sodium salt solution is a saturated solution.

[0108] In some embodiments, the lithium salt solution includes one or more of a lithium chloride solution, a lithium sulfate solution, and a lithium carbonate solution.

[0109] In some embodiments, the concentration of the lithium salt solution is 1 mol / L to 3 mol / L. For example, the concentration of the lithium salt solution includes but is not limited to 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, 3 mol / L, or a range between any two of the foregoing.

[0110] In some embodiments, the surfactant solution includes one or more of dodecyltrimethylammonium bromide solution, tetradecyltrimethylammonium bromide solution, hexadecyltrimethylammonium bromide solution, and octadecyltrimethylammonium bromide solution.

[0111] In some embodiments, the concentration of the surfactant solution is 1 mol / L to 3 mol / L. For example, the concentration of the surfactant solution includes, but is not limited to, 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, 3 mol / L, or a range between any two of the foregoing.

[0112] In some embodiments, the thermally decomposable substance includes one or more of hydrogen peroxide and sodium bicarbonate.

[0113] In some embodiments, after the step of dispersing the intercalated clay in a solution containing a thermally decomposable substance and subjecting the thermally decomposable substance to heat treatment to decompose the thermally decomposable substance to generate gas to peel off the intercalated clay, the step further includes: washing the obtained product, and then sequentially subjecting the product to ultrasonic treatment, a first centrifugal treatment, and a second centrifugal treatment to remove the clay with a multilayer structure to obtain a solution containing single-layer clay nanosheets, wherein the rotation speed of the first centrifugal treatment is higher than the rotation speed of the second centrifugal treatment.

[0114] In some embodiments, the multi-layered structured clay includes one or more of multi-layered structured vermiculite and multi-layered structured montmorillonite.

[0115] In some embodiments, the process conditions of the first centrifugal treatment include: the speed of the centrifugal treatment is 8000rpm~10000rpm, and the time of the centrifugal treatment is 15min~30min. Exemplarily, the speed of the centrifugal treatment includes but is not limited to: 8000rpm, 8200rpm, 8400rpm, 8600rpm, 8800rpm, 9000rpm, 9200rpm, 9400rpm, 9600rpm, 9800rpm, 10000rpm or the range between any two of the foregoing, and the time of the centrifugal treatment includes but is not limited to: 15min, 18min, 20min, 22min, 24min, 26min, 28min, 30min or the range between any two of the foregoing.

[0116] In some embodiments, the process conditions of the second centrifugal treatment include: the speed of the centrifugal treatment is 1000rpm~3000rpm, and the time of the centrifugal treatment is 60min~180min. Exemplarily, the speed of the centrifugal treatment includes but is not limited to: 1000rpm, 1200rpm, 1500rpm, 1800rpm, 2000rpm, 2200rpm, 2400rpm, 2600rpm, 2800rpm, 3000rpm or the range between any two of the foregoing, and the time of the centrifugal treatment includes but is not limited to: 60min, 70min, 80min, 90min, 100min, 110min, 120min, 130min, 140min, 150min, 160min, 170min, 180min or the range between any two of the foregoing.

[0117] In some embodiments, the process conditions of ultrasonic treatment include: the ultrasonic treatment time is 30 min to 60 min. Exemplarily, the ultrasonic treatment time includes but is not limited to: 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, 60 min or a range between any two of the foregoing.

[0118] By adjusting the process conditions of the above-mentioned preparation method, the clay composite membrane provided in one embodiment of the present application can be obtained.

[0119] Another embodiment of the present application provides the use of the above-mentioned clay composite membrane of the present application or the clay composite membrane prepared by the above-mentioned preparation method of the present application in the preparation of separation catalytic membrane.

[0120] Another embodiment of the present application further provides a separation catalytic device, comprising the above-mentioned clay composite membrane of the present application or the clay composite membrane prepared by the above-mentioned preparation method of the present application.

[0121] In some embodiments, the separation catalytic device further comprises one or more of hydrogen peroxide and persulfate. Optionally, hydrogen peroxide or persulfate as an oxidant is beneficial to improve the catalytic degradation effect of the clay composite membrane on micropollutants such as bisphenol A and phenol.

[0122] In some embodiments, the persulfate salt includes one or more of potassium peroxomonosulfate and sodium peroxodisulfate.

[0123] In order to further illustrate the present application, the technical scheme of the present application is described in detail below in conjunction with specific examples. If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in the field or the product instructions are used. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0124] Example 1

[0125] The preparation method of vermiculite composite membrane (clay composite membrane) comprises the following steps:

[0126] Step 1: Add the heat-expanded vermiculite particles into a saturated sodium chloride solution (pretreatment solution), place in an oil bath at 95° C., stir magnetically for 24 hours, and then wash by centrifugation until no chloride ions are detected in the supernatant to obtain intercalated vermiculite;

[0127] Step 2: adding the intercalated vermiculite to a 30wt% hydrogen peroxide aqueous solution (a solution containing a thermally decomposable substance), heating at 95°C for 24 hours to decompose the hydrogen peroxide to generate gas to peel off the intercalated vermiculite, and then washing by centrifugation to obtain a dispersion;

[0128] Step 3: ultrasonically subjecting the dispersion to 60 minutes, centrifuging at 8000 rpm for 30 minutes to remove small-sheet vermiculite nanosheets, and then centrifuging at 2000 rpm for 60 minutes to retain the upper layer of stably dispersed two-dimensional single-sheet vermiculite nanosheet solution (a solution containing single-sheet vermiculite nanosheets);

[0129] Step 4: Take a single-layer vermiculite nanosheet solution, use a polyvinylidene fluoride (PVDF) membrane with an average pore size of 0.22 μm, a diameter of 47 mm, and a thickness of 150 μm as a porous base membrane, use a vacuum filtration device, and orderly assemble the single-layer vermiculite nanosheets on the surface of the porous base membrane by stacking layer by layer, and then dry (heat treat) at 110°C for 48 hours to obtain a two-dimensional vermiculite membrane, which contains multiple layers of stacked single-layer vermiculite nanosheets;

[0130] Step 5: Soak the two-dimensional vermiculite membrane in a 1M cobalt chloride (CoCl2) solution for 24 hours, then clean the surface of the two-dimensional vermiculite membrane with ultrapure water, dry it at 60°C to form a vermiculite layer, and obtain a vermiculite composite membrane.

[0131] The vermiculite composite membrane prepared in Example 1 is composed of a porous substrate membrane and a vermiculite layer located on one side of the porous substrate membrane, wherein the vermiculite layer includes a multi-layer stacked single-layer vermiculite nanosheet and Co nanoparticles attached to the interlayers and the surface of the multi-layer stacked single-layer vermiculite nanosheet. 2+ .

[0132] Example 2

[0133] The preparation method of the vermiculite composite membrane is basically the same as that of Example 1, except that in step 5, the two-dimensional vermiculite membrane is immersed in a 1M cobalt chloride solution for 12 h;

[0134] The vermiculite composite membrane prepared in Example 2 is composed of a porous substrate membrane and a vermiculite layer located on one side of the porous substrate membrane, wherein the vermiculite layer includes a multi-layer stacked single-layer vermiculite nanosheet and Co nanoparticles attached to the interlayers and the surface of the multi-layer stacked single-layer vermiculite nanosheet.2+ .

[0135] Example 3

[0136] The method for preparing the vermiculite composite membrane is basically the same as that in Example 1, except that in step 5, the 1M cobalt chloride solution is replaced with a 1M manganese chloride (MnCl2) solution;

[0137] The vermiculite composite membrane prepared in Example 3 is composed of a porous substrate membrane and a vermiculite layer located on one side of the porous substrate membrane, wherein the vermiculite layer includes a multi-layer stacked single-layer vermiculite nanosheet and Mn nanoparticles attached to the interlayers and the surface of the multi-layer stacked single-layer vermiculite nanosheet. 2+ .

[0138] Example 4

[0139] The method for preparing the vermiculite composite film is basically the same as in Example 1, except that, in step five, the 1M cobalt chloride solution is replaced with 1M copper chloride (CuCl2) solution;

[0140] The vermiculite composite membrane prepared in Example 4 is composed of a porous substrate membrane and a vermiculite layer located on one side of the porous substrate membrane, wherein the vermiculite layer includes a multi-layer stacked single-layer vermiculite nanosheet and Cu 2+ attached to the interlayer and surface of the multi-layer stacked single-layer vermiculite nanosheet. 2+ .

[0141] Example 5

[0142] The method for preparing the vermiculite composite membrane is basically the same as that of Example 1, except that, in step 5, the 1M cobalt chloride solution is replaced with a 1M ferric chloride (FeCl3) solution;

[0143] The vermiculite composite membrane prepared in Example 5 is composed of a porous substrate membrane and a vermiculite layer located on one side of the porous substrate membrane, wherein the vermiculite layer includes a multi-layer stacked single-layer vermiculite nanosheet and Fe2O3 attached to the interlayer and surface of the multi-layer stacked single-layer vermiculite nanosheet. 3+ .

[0144] Example 6

[0145] The preparation method of the vermiculite composite membrane is basically the same as that of Example 1, except that in step 5, the 1M cobalt chloride solution is replaced with a 1M nickel chloride (NiCl2) solution;

[0146] The vermiculite composite membrane prepared in Example 6 is composed of a porous substrate membrane and a vermiculite layer located on one side of the porous substrate membrane, wherein the vermiculite layer includes a multi-layer stacked single-layer vermiculite nanosheet and Ni 2+ .

[0147] Example 7

[0148] The preparation method of montmorillonite composite membrane (clay composite membrane) comprises the following steps:

[0149] Step 1: Add montmorillonite particles to a saturated sodium chloride solution (pretreatment solution), place in an oil bath at 95°C, stir magnetically for 24 hours, and then wash by centrifugation until no chloride ions are detected in the supernatant to obtain intercalated montmorillonite;

[0150] Step 2: adding the intercalated montmorillonite to a 30 wt% hydrogen peroxide aqueous solution (a solution containing a thermally decomposable substance), heating at 95° C. for 24 hours to decompose the hydrogen peroxide to generate gas to peel off the intercalated montmorillonite, and then washing by centrifugation to obtain a dispersion;

[0151] Step 3: ultrasonically subjecting the dispersion to 60 minutes, centrifuging at 8000 rpm for 30 minutes to remove small-layer montmorillonite nanosheets, and then centrifuging at 2000 rpm for 60 minutes to retain the upper layer of stably dispersed two-dimensional single-layer montmorillonite nanosheet solution (a solution containing single-layer montmorillonite nanosheets);

[0152] Step 4: Take a single-layer montmorillonite nanosheet solution, use a polyvinylidene fluoride (PVDF) membrane with an average pore size of 0.22 μm, a diameter of 47 mm, and a thickness of 150 μm as a porous substrate membrane, use a vacuum filtration device, and orderly assemble the single-layer montmorillonite nanosheets on the surface of the porous substrate membrane by stacking layer by layer, and then dry (heat treat) at 110°C for 48 hours to obtain a two-dimensional montmorillonite membrane, which contains multiple layers of stacked single-layer montmorillonite nanosheets;

[0153] Step 5: Soak the two-dimensional montmorillonite membrane in a 1M cobalt chloride (CoCl2) solution for 24 hours, then clean the surface of the two-dimensional montmorillonite membrane with ultrapure water, dry it at 60°C to form a montmorillonite layer, and obtain a montmorillonite composite membrane.

[0154] The montmorillonite composite membrane prepared in Example 7 is composed of a porous substrate membrane and a montmorillonite layer located on one side of the porous substrate membrane, wherein the montmorillonite layer includes a multi-layer stacked monolayer montmorillonite nanosheet and Co attached to the interlayer and surface of the multi-layer stacked monolayer montmorillonite nanosheet. 2+ .

[0155] Example 8

[0156] The preparation method of the vermiculite composite membrane is basically the same as that of Example 1, except that in step 1, the saturated sodium chloride solution is replaced with a 2M lithium chloride solution;

[0157] The vermiculite composite membrane prepared in Example 8 is composed of a porous substrate membrane and a vermiculite layer located on one side of the porous substrate membrane, wherein the vermiculite layer includes a multi-layer stacked single-layer vermiculite nanosheet and Co nanoparticles attached to the interlayers and the surface of the multi-layer stacked single-layer vermiculite nanosheet. 2+.

[0158] Example 9

[0159] The preparation method of the vermiculite composite film is basically the same as that of Example 1, except that in step 1, the saturated sodium chloride solution is replaced with a 2M hexadecyltrimethylammonium bromide solution;

[0160] The vermiculite composite membrane prepared in Example 9 is composed of a porous substrate membrane and a vermiculite layer located on one side of the porous substrate membrane, wherein the vermiculite layer includes a multi-layer stacked single-layer vermiculite nanosheet and Co nanoparticles attached to the interlayers and the surface of the multi-layer stacked single-layer vermiculite nanosheet. 2+ .

[0161] Comparative Example 1

[0162] The preparation method of the vermiculite composite membrane is basically the same as that of Example 1, except that in step 4, the drying temperature is 60°C, and step 5 is omitted; the vermiculite composite membrane prepared in Comparative Example 1 is composed of a porous substrate membrane and a vermiculite layer located on one side of the porous substrate membrane, and the vermiculite layer includes a multi-layer stacked single-layer vermiculite nanosheet. As shown in Figure 6, since the vermiculite composite membrane prepared in Comparative Example 1 cannot exist stably in water, it is impossible to further modify the transition metal ions.

[0163] Comparative Example 2

[0164] The preparation method of the vermiculite composite film is basically the same as in Example 1, except that, in step five, the multi-layer stacked single-layer vermiculite nanosheets are immersed in ultrapure water for 24h and dried at 60 ℃ to obtain a vermiculite composite film;

[0165] The vermiculite composite membrane prepared in Comparative Example 2 consists of a porous base membrane and a vermiculite layer located on one side of the porous base membrane, the vermiculite layer consists of multiple layers of stacked single-layer vermiculite nanosheets, and no transition metal ions are attached between the layers and on the surface of the multiple layers of stacked single-layer vermiculite nanosheets.

[0166] Test Case

[0167] (1) Thickness test of clay nanosheets:

[0168] The thickness of the single-layer vermiculite nanosheet of Example 1 was tested using an atomic force microscope (AFM), and the result is shown in Figure 1. As can be seen from Figure 1, the thickness of the single-layer vermiculite nanosheet is about 1.5 nm, and it is in a single-layer dispersion state, and the sheet diameter of the single-layer vermiculite nanosheet is about 1 μm.

[0169] (2) Morphology test of clay composite film:

[0170] The cross section of the vermiculite composite film prepared in Example 1 was observed using a scanning electron microscope (SEM), and the result is shown in Figure 2. As can be seen from Figure 2, the cross section of the vermiculite composite film presents a multi-layer stacked, highly ordered layered structure, indicating that the preparation method of Example 1 can achieve the exfoliation of a single layer of vermiculite nanosheets and the reorganization of the vermiculite layer.

[0171] (3) Stability test of clay composite membrane:

[0172] The vermiculite composite membrane prepared in Example 1 was placed in organic solvents (ethanol, methanol, n-hexane, acetonitrile, acetone), 1M HCl solution and 1M NaOH solution, and the state of the vermiculite composite membrane was observed after immersion for 0h and 24h, respectively. The results are shown in Figure 3. As can be seen from Figure 3(f) to Figure 3(g), the structure of the vermiculite composite membrane remains stable after being immersed in 1M HCl solution and 1M NaOH solution for 24 hours; in Figure 3(f), VMT is the vermiculite layer and PVDF is the porous substrate membrane. In addition, as can be seen from Figure 3(a) to Figure 3(e), the vermiculite composite membrane can also maintain structural stability in a variety of organic solvents, proving its excellent chemical stability.

[0173] Figure 4 (a) is a picture of the monolayer montmorillonite nanosheet solution prepared in step 3 of Example 7. It can be seen from the figure that the monolayer montmorillonite nanosheet is dispersed relatively evenly in the solution. Figure 4 (b) is a picture of the montmorillonite composite film prepared in Example 7. The montmorillonite composite film prepared in Example 7 is placed in water, and the result is shown in Figure 5. Figure 5 shows that the montmorillonite composite film prepared in Example 7 can exist stably in water.

[0174] The vermiculite composite membrane prepared in Comparative Example 1 was placed in water, and the result was shown in Figure 6. Figure 6 shows that the vermiculite composite membrane prepared in Comparative Example 1 could not exist stably in water.

[0175] (4) Surface properties and interlayer spacing test of clay composite membrane:

[0176] The surface water contact angle of the vermiculite composite membranes of Example 1, Examples 3 to 6 and Comparative Example 2 was tested, the surface potential of the vermiculite composite membranes of Example 1 and Examples 3 to 6 was tested, and the vermiculite composite membranes of Example 1 and Examples 3 to 6 were tested using an X-ray diffractometer to obtain the interlayer spacing of the vermiculite composite membranes. The test results are shown in Figures 7 to 9 respectively.

[0177] As can be seen from Figures 7 to 9, the surface properties and internal structures of the vermiculite composite membranes of Examples 1 and Examples 3 to 6 can be controlled. Compared with the vermiculite composite membrane of Comparative Example 2, the surface negative charge of the vermiculite composite membrane of Example 1 is stronger, its surface potential is -28.92 mV, it is more hydrophobic, the surface water contact angle is 37.8°, and the interlayer spacing is slightly increased to 1.42 nm; the surface potential of the vermiculite composite membrane of Example 3 is -18.36 mV, and the surface water contact angle is 27. 4°, and the interlayer spacing is 1.44nm; the surface potential of the vermiculite composite membrane of Example 4 is -24.80mV, the surface water contact angle is 47.6°, and the interlayer spacing is 1.35nm; the surface potential of the vermiculite composite membrane of Example 5 is -17.73mV, the surface water contact angle is 39.4°, and the interlayer spacing is 1.52nm; the surface potential of the vermiculite composite membrane of Example 6 is -21.5mV, the surface water contact angle is 35.7°, and the interlayer spacing is 1.39nm.

[0178] (5) Test on the degradation of pollutants by clay composite membrane:

[0179] The vermiculite composite membranes of Example 1, Examples 3 to 6 and Comparative Example 2 and the montmorillonite composite membrane of Example 7 were respectively placed in high pressure filtration devices, and a bisphenol A (BPA) solution (10 μM) containing potassium permonosulfate (PMS, 100 mg / L) was filtered. By detecting the filtrate, it was found that the removal rate of BPA in Comparative Example 2 was about 32%, the removal rate of BPA in Example 1 and Examples 3 to 6 reached more than 40%, and the removal rate of BPA in Example 7 was about 95%. In particular, no BPA molecules were present in the filtrate of Example 1, and the removal rate of BPA in Example 1 reached 100%, which proved that the vermiculite composite membranes of Examples 1, Examples 3 to 6 and the montmorillonite composite membrane of Example 7 can achieve in-situ degradation of BPA, and the degradation efficiency of BPA is relatively high. The results are shown in FIG. 10 .

[0180] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0181] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be construed as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent application shall be subject to the attached claims, and the description may be used to interpret the content of the claims.

Claims

1. A clay composite film, characterized in that: It comprises a porous substrate membrane and a clay layer at least located on one side of the porous substrate membrane, wherein the clay layer comprises multi-layer stacked monolayer clay nanosheets and transition metal ions attached to the interlayers and surfaces of the multi-layer stacked monolayer clay nanosheets.

2. The clay composite membrane according to claim 1, characterized in that: The clay composite film has at least one of the following characteristics (1) to (8): (1) The transition metal ion includes Co 2+ , Mn 2+ , Fe 2+ , Fe 3+ , Cu 2+ and Ni 2+ One or more of; (2) The thickness of the clay layer is 15 nm to 500 nm; (3) The thickness of the single-layer clay nanosheet is 0.5 nm to 2 nm; (4) The single-layer clay nanosheet has a sheet diameter of 1 μm to 10 μm; (5) The monolithic clay nanosheets include one or more of monolithic vermiculite nanosheets and monolithic montmorillonite nanosheets; (6) The average pore size of the pore structure of the porous substrate membrane is 0.1 μm to 0.45 μm; (7) The thickness of the porous substrate membrane is 2 μm to 500 μm; (8) The material of the porous substrate membrane includes one or more of polyvinylidene fluoride, polyethersulfone and ceramic.

3. A method for preparing a clay composite film, characterized in that: The steps include: The clay is placed in different solutions, and subjected to stirring and washing treatments to prepare a solution containing single-layer clay nanosheets; Assembling the solution containing the monolayer clay nanosheets layer by layer on at least one side of the porous substrate membrane, and subjecting it to heat treatment, to obtain a two-dimensional clay membrane, wherein the two-dimensional clay membrane contains multiple layers of stacked monolayer clay nanosheets; Placing the two-dimensional clay film in a transition metal salt solution, so that the transition metal ions in the transition metal salt solution adhere to the interlayers and surfaces of the multi-layer stacked single-layer clay nanosheets to form a clay layer, thereby obtaining the clay composite film; The clay composite membrane comprises the porous substrate membrane and the clay layer at least located on one side of the porous substrate membrane, and the clay layer comprises the multi-layer stacked single-layer clay nanosheets and the transition metal ions.

4. The preparation method according to claim 3, characterized in that: The preparation method meets at least one of the following conditions (1) to (9): (1) The transition metal ion includes Co 2+ , Mn 2+ , Fe 2+ , Fe 3+ , Cu 2+ and Ni 2+ One or more of; (2) The thickness of the clay layer is 15 nm to 500 nm; (3) The thickness of the single-layer clay nanosheet is 0.5 nm to 2 nm; (4) The single-layer clay nanosheet has a sheet diameter of 1 μm to 10 μm; (5) The monolithic clay nanosheets include one or more of monolithic vermiculite nanosheets and monolithic montmorillonite nanosheets; (6) The process conditions of the heat treatment include: the heat treatment temperature is 100°C to 150°C, and the heat treatment time is 12h to 48h; (7) The concentration of the solution containing the single-layer clay nanosheet is 0.1 mg / mL to 1 mg / mL; (8) The material of the porous substrate membrane includes one or more of polyvinylidene fluoride, polyethersulfone and ceramic; (9) The step of assembling the solution containing the single-layer clay nanosheets on at least one side of the porous substrate membrane layer by layer includes: assembling the solution containing the single-layer clay nanosheets on at least one side of the porous substrate membrane layer by layer using at least one method selected from the group consisting of suction filtration, spraying, drop coating, and spin coating.

5. The preparation method according to claim 3 or 4, characterized in that: The steps of placing clay in different solutions, stirring and washing, and preparing a solution containing single-layer clay nanosheets include: The clay is placed in a pretreatment solution, and subjected to stirring treatment and washing treatment in sequence to prepare intercalated clay; The intercalated clay is dispersed in a solution containing a thermally decomposable substance, and the thermally decomposable substance is decomposed by heating to generate gas to peel off the intercalated clay, thereby obtaining the solution containing the single-layer clay nanosheet.

6. The preparation method according to claim 5, characterized in that: The method for preparing the solution containing monolayer clay nanosheets meets at least one of the following conditions (1) to (5): (1) The process conditions of the stirring treatment include: a stirring temperature of 25°C to 120°C and a stirring time of 12h to 48h; (2) The process conditions of the heating treatment include: a heating temperature of 90°C to 120°C and a heating time of 12h to 48h; (3) The clay comprises one or more of thermally expanded vermiculite and montmorillonite, and the intercalated clay comprises one or more of intercalated vermiculite and intercalated montmorillonite; (4) The pretreatment solution includes one or more of a sodium salt solution, a lithium salt solution and a surfactant solution; the sodium salt solution includes one or more of a sodium chloride solution, a sodium sulfate solution, a sodium carbonate solution and a sodium bicarbonate solution; the lithium salt solution includes one or more of a lithium chloride solution, a lithium sulfate solution and a lithium carbonate solution; the surfactant solution includes one or more of a dodecyltrimethylammonium bromide solution, a tetradecyltrimethylammonium bromide solution, a hexadecyltrimethylammonium bromide solution and an octadecyltrimethylammonium bromide solution; optionally, the sodium salt solution is a saturated solution; optionally, the concentration of the lithium salt solution is 1 mol / L to 3 mol / L; optionally, the concentration of the surfactant solution is 1 mol / L to 3 mol / L; (5) The thermally decomposable substance includes one or more of hydrogen peroxide and sodium bicarbonate.

7. The preparation method according to claim 5, characterized in that: After the step of dispersing the intercalated clay in a solution containing a thermally decomposable substance, and subjecting the thermally decomposable substance to heating treatment to decompose the thermally decomposable substance to generate gas to peel off the intercalated clay, the method further includes: washing the obtained product, and then subjecting the obtained product to ultrasonic treatment, first centrifugal treatment, and second centrifugal treatment in sequence to remove the clay with a multilayer structure, thereby obtaining a solution containing single-layer clay nanosheets, wherein the rotation speed of the first centrifugal treatment is higher than the rotation speed of the second centrifugal treatment; Optionally, the process conditions of the first centrifugal treatment include: a centrifugal treatment speed of 8000 rpm to 10000 rpm, and a centrifugal treatment time of 15 min to 30 min; Optionally, the process conditions of the second centrifugal treatment include: a centrifugal treatment speed of 1000 rpm to 3000 rpm, and a centrifugal treatment time of 60 min to 180 min; Optionally, the process conditions of the ultrasonic treatment include: the ultrasonic treatment time is 30min~60min.

8. Use of the clay composite membrane according to any one of claims 1 to 2 or the clay composite membrane prepared by the preparation method according to any one of claims 3 to 7 in the preparation of separation catalytic membranes.

9. A separation catalytic device, characterized in that: It comprises the clay composite film described in any one of claims 1 to 2 or the clay composite film prepared by the preparation method described in any one of claims 3 to 7.

10. The separation catalytic device according to claim 9, characterized in that: The separation catalytic device also includes one or more of hydrogen peroxide and persulfate.

Citation Information

Patent Citations

  • Preparation method of high-throughput bacteriostatic doped hectorite-metal ion reverse osmosis composite membrane

    CN108854587A

  • Vermiculite-based ion screening film and preparation method thereof

    CN111389225A

  • Preparation method of two-dimensional clay-based separation membrane for water treatment

    CN114832635A

  • Natural vermiculite layered film for efficiently separating polar and non-polar solvents

    CN114870649A

  • Composite membrane for heavy metal pollution treatment and preparation method thereof

    CN117181008A

Cited By

  • Preparation method of membrane, membrane, and method, device and method for measuring air inlet value of membrane

    CN121715067A